Incidence and mitigation of gastrointestinal events in patients with relapsing–remitting multiple sclerosis receiving delayed-release dimethyl fumarate: a German phase IV study (TOLERATE). (16th April 2018) - Gold, Ralf; Schlegel, Eugen; Elias-Hamp, Birte; Albert, Christian; Schmidt, Stephan; Tackenberg, Björn; Xiao, James; Schaak, Tom; Salmen, Hans Christian
Background: Gastrointestinal (GI) events are common adverse events (AEs) associated with delayed-release dimethyl fumarate (DMF), an approved treatment for relapsing–remitting multiple sclerosis (RRMS). The objective of the TOLERATE study was to evaluate GI tolerability and GI mitigation via symptomatic therapies in patients initiating DMF in a real-world clinical setting in Germany. Methods: TOLERATE was a multicentre, open-label, single-arm study performed at 25 German sites. Endpoints were frequency, severity, duration (all primary) and mitigation of GI-related events (secondary). Patients were instructed to take DMF according to the prescribing information for up to 12 weeks and to document GI events and intake of GI-symptomatic therapy on numerical rating scales, using eDiaries. Results: A total of 211 patients were included in the safety population (71% female; mean age 40 ± 11 years). Of these, 185 patients (87.7%) reported GI-related events, out of which nearly half received GI-symptomatic therapy (84/185; 45.4%). The most frequently reported GI events were upper abdominal pain, flatulence and nausea. GI-related events peaked during the first 3 weeks of therapy and rapidly decreased thereafter. The severity of GI events over 12 weeks according to the Modified Overall Gastrointestinal Symptom Scale were mild to moderate in the majority of patients reporting GI-related events and taking symptomatic GI medication (53.6%). Only 10% of all patients discontinued study treatment due to AEs in general, while 6.6% discontinued due to GI-related events. The severity of GI-related events decreased over time in patients who received symptomatic treatment with one or more medications (e.g. acid secretion blockers, antidiarrhoeals or antiemetics). Conclusion: Gastrointestinal events associated with delayed-release DMF were mainly mild to moderate in severity. Prevalence of GI events peaked during the first 3 weeks of therapy and rapidly faded thereafter. Although 44.9% of patients experiencing GI events used common GI symptomatic therapies, only 6.6% of patients discontinued DMF because of GI events, suggesting that GI events could be managed well with common symptomatic therapy.